2003
DOI: 10.1103/physrevb.67.054417
|View full text |Cite
|
Sign up to set email alerts
|

First-principles calculations of spin spirals inNi2MnGaandNi2

Abstract: We report here noncollinear magnetic configurations in the Heusler alloys Ni 2 MnGa and Ni 2 MnAl which are interesting in the context of the magnetic shape memory effect. The total energies for different spin spirals are calculated and the ground-state magnetic structures are identified. The calculated dispersion curves are used to estimate the Curie temperature which is found to be in good agreement with experiments. In addition, the variation of the magnetic moment as a function of the spiral structure is s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 34 publications
5
47
1
Order By: Relevance
“…The magnetic measurements have shown that addition of Fe or Co instead of Ni results in increase of Curie temperature T C . This observation together with the theoretical suggestion 25) gives a basic ground for the development of high temperature ferromagnetic shape memory alloys in the Ni-Mn-Ga system.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The magnetic measurements have shown that addition of Fe or Co instead of Ni results in increase of Curie temperature T C . This observation together with the theoretical suggestion 25) gives a basic ground for the development of high temperature ferromagnetic shape memory alloys in the Ni-Mn-Ga system.…”
Section: Resultsmentioning
confidence: 99%
“…The experimentally observed increase of T C in Ni 2:16Àx Co x Mn 0:84 Ga and Ni 2:20Àz Fe z Mn 0:80 Ga is in accordance with a recent theoretical consideration of magnetic properties of Ni 2 MnGa and Ni 2 MnAl. 25) In Ref. 25) a suggestion was made that Ni significantly affects T C in these alloys and, therefore, Curie temperature in Ni 2 MnGa could be increased by a substitution of the Ni sites.…”
Section: Nominal Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 The mixed B2 / L2 1 of Ni 2 MnAl has been used to produce negative magnetoresistance ratio in granular films. 19 First-principles calculations by Enkovaara et al on Ni 2 MnAl have confirmed the FM character of the L2 1 structure, 20 while Büsgen and collaborators have shown that the Ni 50 Mn x Al 50−x is FM from 14 to 31 at. % of Mn.…”
mentioning
confidence: 99%
“…20,21 In MSM alloys, an external magnetic field can induce large strains when applied in the martensitic state. 22 The MSM alloys are of great interest as promising smart materials for future technological applications. 20,[23][24][25] They can be used as sensors and actuators in different fields of applications.…”
Section: Introductionmentioning
confidence: 99%